Administrasi kepala Sekolah dalam Supervisi Akademik untuk Meningkatkan Kinerja Guru di MTs Lokus: MTs Al Hikmah Karawang - Ayi Najmul Hidayat; Sobari Sobari; Irma Restiana (SENTRI: Jurnal Riset Ilmiah, 2026)
This study focuses on analyzing the role of the principal's administrative management in academic supervision as a strategic effort to improve teacher performance at Madrasah Tsanawiyah (MTs). Academic supervision is viewed not merely as an evaluative activity, but as a comprehensive administrative process that supports professional development and continuous improvement among teachers. To achieve this objective, the study employed a qualitative research approach with data collected through three main techniques. First, in-depth interviews were conducted to obtain detailed information regarding the planning, implementation, and evaluation of the principal's administrative practices in academic supervision. Second, direct observations were carried out to examine how supervisory planning, implementation, and evaluation were applied in real school settings. Third, document analysis was used to review relevant administrative documents, including supervision plans, implementation records, and evaluation reports prepared by the principal. Data were analyzed using the interactive analysis model developed by Miles and Huberman, which involves data reduction, data display, and the drawing and verification of conclusions. This analytical approach enabled the researcher to systematically interpret complex qualitative data and identify meaningful patterns related to supervisory administration. To ensure the credibility and trustworthiness of the findings, data validity was strengthened through source triangulation and technique triangulation, as well as member checking with key informants to confirm the accuracy of interpretations. The findings reveal that well-organized administrative management of academic supervision, covering systematic planning, implementation, documentation, reporting, evaluation, and follow-up, plays a significant role in enhancing teacher performance at MTs. However, several key challenges were identified during the implementation process, including time constraints due to the principal's multiple administrative responsibilities and the lack of standardized supervision instruments. To address these obstacles, the principal implemented several strategic solutions: delegating certain supervisory tasks to senior teachers, developing flexible supervision schedules, and creating contextualized supervision instruments adapted to the specific needs of the madrasah. Effective supervisory administration encourages teachers to improve their instructional practices, thereby contributing positively to the overall quality of learning.